The changing role of the law enforcement analyst: clarifying core competencies for analysts and supervisors through empirical research - Weston, Crystal (Policing and society, 2020)
Enhanced opportunities to use new techniques to derive insights from large volumes of data have potential to change the role of the law enforcement analyst. Alongside this growing potential is a push toward professionalisation for crime and intelligence analysis as an occupation. In this paper, we explore the extent to which existing descriptions of core competencies reflect skills identified as important by analysts and their managers. We draw on interviews with sixty-one analysts and supervisors from law enforcement agencies in Canada, the United States, and Australia. We confirm that existing descriptions of core competencies align with those identified by analysts and managers. We identify three considerations for present-day police organisations: the importance of data literacy and technical skills, the importance of self-motivation as a trait for analysts, and the core competencies of analyst supervisors. We complicate discussions about the importance of technological comprehension in light of software that automates components of analysis, illustrating how limits in data literacy translate to challenges for making effective use of new technologies. Next, we demonstrate how an ability to navigate interpersonal dynamics in police organisations is essential for analysts and analytic managers to be effective in their roles. We illustrate a reliance on individual-level motivation for competency-building over organisationally driven or standardised professionalisation. Finally, we contribute to limited scholarship addressing competencies for analyst supervisors and managers and discuss the implications of supervision for analyst skill development.